Gestational Diabetes Mellitus pregnancy by pregnancy: early, late and nonrecurrent GDM. (June 2022) - Giuliani, Chiara; Sciacca, Laura; Biase, Nicolina Di; Tumminia, Andrea; Milluzzo, Agostino; Faggiano, Antongiulio; Romana Amorosi, Francesca; Convertino, Alessio; Bitterman, Olimpia; Festa, Camilla; Napoli, Angela
Abstract: Aims: To assess the GDM recurrence rate in a cohort of pregnant women with prior GDM, to compare two consecutive pregnancies complicated by GDM, to compare women with nonrecurrent and recurrent GDM and to stratify the latter in women with early and late recurrent GDM. Methods: Retrospective study including 113 women with GDM in an index pregnancy (G1), at least a postindex pregnancy (G2) and normal glucose tolerance in between. The GDM recurrence rate was assessed, and maternal and neonatal outcomes and pancreatic beta cell function of the index pregnancy were compared with those of the postindex pregnancy (G1 vs. G2). Women with nonrecurrent GDM were compared with those with recurrent GDM. Results: The GDM recurrence rate was 83.2% and the minimum prevalence of early recurrent GDM was 43, 4%. The pregravid BMI of women with recurrent GDM increased between the two pregnancies (27.3 ± 5.98 vs. 28.1 ± 6.19 kg/m 2, p < 0.05). Women with recurrent GDM had a higher prepregnancy BMI than those with nonrecurrent GDM either at the index (27.3 ± 5.98 vs. 23.1 ± 4.78 kg/m 2, p < 0.05) or the postindex pregnancy (27 ± 6vs.24 ± 4, 4 kg/m 2, p < 0.05). Conclusions: GDM shows a high recurrence rate in our cohort of slightly overweight women, with an early GDM minimum prevalence of 43.4%.